2023
DOI: 10.3390/antiox12030615
|View full text |Cite
|
Sign up to set email alerts
|

Differential Apoptotic Effects of Bee Product Mixtures on Normal and Cancer Hepatic Cells

Abstract: Most effective anticancer drugs normally generate considerable cytotoxicity in normal cells; therefore, the preferential activation of apoptosis in cancer cells and the reduction of toxicity in normal cells is a great challenge in cancer research. Natural products with selective anticancer properties used as complementary medicine can help to achieve this goal. The aim of the present study was to analyze the effect of the addition of bee products [propolis (PR) or royal jelly (RJ) or propolis and royal jelly (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…50,51 In contrast, even application of 100 mg mL −1 RJ did not cause apoptosis in HepG2 and WRL-68 cells. 52 This contradiction may be related to the different origins and compositions of the royal jelly samples since the environmental and biological factors, including season, plant type, ambient conditions, and the time after larval transfer, could all have a huge impact on their content. 53 The increased late apoptotic percentage of both glioblastoma and neuroblastoma cell lines proved that application of 10 mg mL −1 RJ stimulated the cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…50,51 In contrast, even application of 100 mg mL −1 RJ did not cause apoptosis in HepG2 and WRL-68 cells. 52 This contradiction may be related to the different origins and compositions of the royal jelly samples since the environmental and biological factors, including season, plant type, ambient conditions, and the time after larval transfer, could all have a huge impact on their content. 53 The increased late apoptotic percentage of both glioblastoma and neuroblastoma cell lines proved that application of 10 mg mL −1 RJ stimulated the cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have shown that gallic acid, quercetin, and ellagic acid are able to inhibit cancer cell proliferation at levels similar to what is present in YSH [4,12.18,46]. Other studies have also identified YSH components such as carvacol, thymol, catechin, and some sulfatide compounds as being active in killing cancer cells [46][47][48]. A more comprehensive study of a larger number of different honey samples with a wider range of identified standards would be useful for verifying that YSH samples have a more unique pattern of chemical composition which can be used to distinguish them from other types of honey and which could be used to identify likely anti-cancer components.…”
Section: Discussionmentioning
confidence: 99%
“…A TUNEL assay was used to measure DNA destruction in the final stages of apoptosis [ 27 ]. The overnight-cultured cells were treated or co-treated with H 2 O 2 for 24 h. Untreated LMHs served as the control.…”
Section: Methodsmentioning
confidence: 99%